Next-generation flexible formats of VNAR domains expand the drug platform's utility and developability. (17th December 2018) - Ubah, Obinna C.; Buschhaus, Magdalena J.; Ferguson, Laura; Kovaleva, Marina; Steven, John; Porter, Andrew J.; Barelle, Caroline J.
Abstract : Therapeutic mAbs have delivered several blockbuster drugs in oncology and autoimmune inflammatory disease. Revenue for mAbs continues to rise, even in the face of competition from a growing portfolio of biosimilars. Despite this success, there are still limitations associated with the use of mAbs as therapeutic molecules. With a molecular mass of 150 kDa, a two-chain structure and complex glycosylation these challenges include a high cost of goods, limited delivery options, and poor solid tumour penetration. There remains an urgency to create alternatives to antibody scaffolds in a bid to circumvent these limitations, while maintaining or improving the therapeutic success of conventional mAb formats. Smaller, less complex binders, with increased domain valency, multi-specific/paratopic targeting, tuneable serum half-life and low inherent immunogenicity are a few of the characteristics being explored by the next generation of biologic molecules. One novel 'antibody-like' binder that has naturally evolved over 450 million years is the variable new antigen receptor (VNAR) identified as a key component of the adaptive immune system of sharks. At only 11 kDa, these single-domain structures are the smallest IgG-like proteins in the animal kingdom and provide an excellent platform for molecular engineering and biologics drug discovery. VNAR attributes include high affinity for target, ease of expression, stability, solubility, multi-specificity, and increased potential for solid tissue penetration. This review article documents the recent drug developmental milestones achieved for therapeutic VNARs and highlights the first reported evidence of the efficacy of these domains in clinically relevant models of disease.